2010
DOI: 10.5307/jbe.2010.35.5.323
|View full text |Cite
|
Sign up to set email alerts
|

Functional Shock Responses of the Pear According to the Combination of the Packaging Cushioning Materials

Abstract: Physical damages on fruits may be caused by shock and vibration inputs that transmitted from the transporting vehicle through the packaging and cushioning materials to the fruit. In this study, both half sine shock test and trapezoidal shock test were performed by MIL-STD-810F specification in order to investigate and represent the shock response properties such as peak acceleration and shock amplification factors of the pear according to packaging and cushioning materials for optimal packaging design during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Based on PSD measurements taken during transport of loquat from Spain to Italy, simulated transport vibration using an electro-dynamic shaker showed that most loquats suffered a decline in quality owing to vibration pressure and frictional stress (Barchi et al, 2002). Damage to produce owing to transport vibration has also been demonstrated for tomatoes (Olorunda and Tung, 1985;Singh and singh, 1992), potatoes Turczyn et al, 1986), peaches (Vergano et al, 1991;Choi et al, 2010), apples (Schulte et al, 1990;Singh and Xu, 1993;VURSAVUŞ and ÖZGÜVEN, 2004), and pears Berardinelli et al, 2005;Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on PSD measurements taken during transport of loquat from Spain to Italy, simulated transport vibration using an electro-dynamic shaker showed that most loquats suffered a decline in quality owing to vibration pressure and frictional stress (Barchi et al, 2002). Damage to produce owing to transport vibration has also been demonstrated for tomatoes (Olorunda and Tung, 1985;Singh and singh, 1992), potatoes Turczyn et al, 1986), peaches (Vergano et al, 1991;Choi et al, 2010), apples (Schulte et al, 1990;Singh and Xu, 1993;VURSAVUŞ and ÖZGÜVEN, 2004), and pears Berardinelli et al, 2005;Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Komponen getaran pada kendaraan yang memiliki pengaruh yang terbesar adalah getaran secara vertikal (Vursavus dan Ozguven 2004). Kerusakan pada produk yang disebabkan oleh getaran transportasi telah dilakukan pada buah persik (Choi et al 2010), apel (Vursavus dan Ozguven 2004), dan buah pir (Berardinelli et al 2005;Kim et al 2010).…”
Section: Pendahuluanunclassified
“…According to Pangidoan et al [4], the result of storage and packaging of weight loss in chilies reached 2.5%. Shocks that occur during long-distance transport on transportation can result in mechanical damage, weight loss and shorten shelf life [5,19,20,21]. Storage of fresh curly chilies is IOP Publishing doi:10.1088/1755-1315/1024/1/012014 2 carried out not to improve the quality of the chilies but to maintain the quality of fresh curly chilies [4].…”
Section: Introductionmentioning
confidence: 99%